Students’ Perceptions Related to the Value of Intralingual Dubbing Activities as a Motivational Tool for the Enhancement of Oral Skills in EFL Learning - Baeyens, Lucas (Journal of Audiovisual Translation, 2024)
Didactic Audiovisual Translation (DAT) can contribute a myriad of engaging and inspiring activities to foreign language (FL) education. One of the most inspiring modes is intralingual dubbing (ID), which can become a powerful and effective ally to practice and improve, among others, general oral skills such as pronunciation or intonation. Even though the design and implementation of ID activities have been studied over the past decade, their potential in aiding English as a Foreign Language (EFL) learning environments is still largely unknown (Lertola, 2019). For this reason, this paper examines the implementation of ID exercises with 38 intermediate-level EFL students from Spain. The study focuses, through the collection and analysis of quantitative and qualitative data, on the participants’ perspectives on dubbing tasks as a potentially innovative, motivating, and useful tool for improving oral skills. In terms of perceived usefulness, 94.7% considered ID as “absolutely” or “quite” beneficial for their speaking skills, in line with previous research (Talaván & Costal, 2017). The results offered additional insights on ID’s engaging and innovative value, with 95% of participants expressing very favourable opinions towards the task. Lay summary This paper revolves around the application of intralingual dubbing activities in the foreign language classroom. This dubbing modality involves the replacement of the audio track of a video clip with another created by the students in the same language as the original. To this effect, the paper highlights the importance of preparation prior to the activity, as well as the beneficial effects that may arise after the task. Therefore, firstly, a brief theoretical framework is provided, highlighting the most important research on the implementation of intralingual dubbing in language learning and the relevance of oral skills and pronunciation, with special emphasis on the notions of intelligibility or English as a lingua franca. Next, a proposal for selection criteria to obtain relevant and motivating clips that can be usefully applied in intralingual dubbing tasks is offered, to provide a practical tool for teachers and researchers. On the other hand, the paper includes an analysis of the opinions and perspectives offered by a group of students after carrying out dubbing activities, to study their motivating and pedagogical value in the development of oral skills. These opinions revealed that, in general, the use of dubbing was perceived as an inspiring, attractive, fun, and useful resource to improve their oral skills, intonation and pronunciation.